Endothelin-1 increases susceptibility of isolated rat hearts to ischemia/reperfusion injury by reducing coronary flow. - Groot, d; Illing, B; Horn, M; Urban, B; Haase, A; Schnackerz, K; Neubauer, S (1998)
Endothelin-1 (ET-1) is the most potent vasoconstrictor known to date, and it was proposed that this peptide plays a major role in myocardial ischemia/reperfusion injury. ET-1 could increase myocardial susceptibility to ischemia by two mechanisms: via coronary flow reduction and/or via direct, metabolic effects on the heart. In isolated, buffer-perfused rat hearts, function was measured with a left ventricular balloon, and energy metabolism (ATP, phosphocreatine, inorganic phosphate, intracellular pH) was estimated by 31NMR-spectroscopy. Under constant pressure perfusion, hearts were subjected to 15 min of control perfusion, 15 ("moderate injury") or 30 ("severe injury") min of global ischemia, followed by 30 min of reperfusion. Hearts were pre-treated with ET-1 (boluses of 0.04, 4, 40 of 400 pmol) 5 min prior to ischemia. In the control period, ET-1 reduced coronary flow, ventricular function, phosphocreatine and intracellular pH dose-dependently: during ischemia/reperfusion, coronary flow, functional recovery and high-energy phosphate metabolism were adversely affected by ET-1 in a dose-related manner. To study effects of ET-1 not related to coronary flow reduction, additional hearts were perfused under constant flow conditions (ET-1 0 or 400 pmol) during 15 min of control, 15 min of ischemia and 30 min of reperfusion. When coronary flow was held constant, functional and energetic parameters were similar for untreated and ET-1 treated hearts during the entire protocol, i.e. the adverse effects of ET-1 on function and energy metabolism during ischemia/reperfusion were completely abolished. In both constant pressure and constant flow protocols, 400 pmol ET-1 reduced the extent of ischemic intracellular acidosis. The authors conclude that ET-1 increases the susceptibility of isolated hearts to ischemia/reperfusion injury via reduction of coronary flow.